Polymer insulation of ultramicro carbon fiber electrodes for electrophysiological, electrochemical and biosensor applications - Budai, Dénes; Horváth, Klára; Szabó, András (Acta Biologica Szegediensis, 2007)
There is an obvious need for electrodes with extremely small electroactive areas and structural dimensions that offer great promise for electrochemical microscopy used for neuronal analysis in ultrasmall environments. In the present study we have developed ultramicro carbon fiber (CF) electrodes with combined thin layers of poly(oxyphenylene) and epoxy resin coatings for electrical insulation. The thickness of the borosilicate glass housing and insulating layer of our standard CF microelectrodes is about 1 |im and the carbon tip protrudes by about 20 |im from the glass assembly. Functionalization requires longer sections of the exposed, uninsulated carbon fiber where submicron tips are shaped and chemical modifications are made. Electrodeposition of poly(oxyphenylene) was carried out using anodic currents at 2V against an Ag/AgCI half-cell. After finishing the polymerization at 150°C for 2 hours, electrical impedances of the electrodes were 17.1 ±2.8MQ (mean ± SD, n= 22). An additional epoxy coating was formed by dipping the CF electrodes in diluted epoxy resins followed by dipping in a mixture of diluted curing agents. The epoxy layer significantly increased the effectiveness of the insulation as the impedance for each of the 38 prepared CF electrodes was higher than the upper range limit (200 MQ) of our impedance meter. The thickness of the combined insulating layer was less than 1 |im as estimated by electron microscopic studies. Removal of the insulation from the very tip was carried out using high voltage spark or electrochemical etching. These submicron CF electrodes are suitable for extracellular spike recording, electrochemical and biosensor applications.